Effects of Asymmetries on the Dynamics of Motorized Momentum Exchange Tether and Payloads Injection Precision - Naiming Qi; Yong Yang; Jun Zhao; Qilong Sun; Wenhui Zhang (International Journal of Aerospace Engineering)
This paper presents the error dynamic model of motorized momentum exchange tether (MMET) based on the momentum exchange principle of space tether. The error dynamics are caused by the structural bias of the differences in tethers’ length and the difference in payloads’ mass. After that, the coupling analysis between orbit and attitude is presented. It is shown that, with increasing the differences in tethers’ length and payloads’ mass, the COM deviation of the MMET increases linearly. The numerical simulations of the MMET by considering the structural asymmetries are presented; the results show that the asymmetries have tiny influences on the orbit of the chief satellite by decreasing the apogee, which will change the instantaneous velocity at the apogee and affect the payload injection precision. What is more, the structural asymmetries have effects on the attitude elements (including the pitch angle and yaw angle); however, the effects could be weakened by the external torque. The structural asymmetries and gravity gradient torque have composite effects on the angular velocity of the propulsion tether.